2020
DOI: 10.1007/s40314-020-1131-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-objective quantum particle swarm algorithm for suspension optimization

Abstract: In this paper, a novel multi-objective archive-based Quantum Particle Optimizer (MOQPSO) is proposed for solving suspension optimization problems. The algorithm has been adapted from the well-known single objective QPSO by substantial modifications in the core equations and implementation of new multi-objective mechanisms. The novel algorithm MOQPSO and the long-established NSGA-II and COGA-II (Compressed-Objective Genetic Algorithm with Convergence Detection) are compared. Two situations are considered in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…To ensure ride comfort, the dynamic load on the suspension should overcome the friction force most of the time. Thus, our discussion focuses on the case of small friction force, of which a general dynamic equation of the 2-DOF system is 24 No 5 a Numerical simulation Yes (stochastic) Wang et al 16 No 1 Numerical simulation Yes Shangguan et al 15 No 2 Numerical simulation No Grotti et al 22 No…”
Section: Seat Model With Frictionmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure ride comfort, the dynamic load on the suspension should overcome the friction force most of the time. Thus, our discussion focuses on the case of small friction force, of which a general dynamic equation of the 2-DOF system is 24 No 5 a Numerical simulation Yes (stochastic) Wang et al 16 No 1 Numerical simulation Yes Shangguan et al 15 No 2 Numerical simulation No Grotti et al 22 No…”
Section: Seat Model With Frictionmentioning
confidence: 99%
“…It is a fixed-point problem because s v 01 depends on the overall equivalent damping c e . With equations (22) and (25), c e can be determined from given c 1 , k 1 , and f.…”
Section: Gaussian Equivalent Linearizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, less information regarding the influence of weighting matrices on the closed-loop presentation has inspired scientists to look into the efficiency of swarm intelligence techniques handling the LQR weight selection problem. A novel multiobjective archived based quantum particle optimizer (MOQPSO) is introduced and compared with the long-established COGA-II and NSGA-II algorithm on a half car and a bus suspension system [11].…”
Section: Introductionmentioning
confidence: 99%
“…These models can be categorized into three groups of quarter, 1416 half 1720 and full-vehicle models. 2125 Naturally, if the vehicle model in simulation is more complete, the dynamic response obtained from the model will be more reliable. Fossati et al 26 showed that a full vehicle model under random road excitations with optimized suspension parameters can have a better performance in comparison with non-optimized one.…”
Section: Introductionmentioning
confidence: 99%